A case study of development of a mobile application from an existing web information system. Issue 1 (18th April 2016) - Barroca Filho, Itamir de Morais; Aquino Júnior, Gibeon Soares
Abstract : Purpose: This paper aims to present a case study of the Metamorphosis process in the development of a mobile application based on an existing web information system. Design/methodology/approach: The paper presents the design and execution of a case study to investigate the feasibility of using the Metamorphosis process to create mobile applications based on existing web information systems. This case study reports the development of a mobile version from SIGEventos web information system. Findings: The use of Metamorphosis process for the development of SIGEventos Mobile, based on SIGEventos web version, allowed the investigation of the feasibility of it on creation of mobile applications based on existing web information systems. This process was considered useful for creating mobile applications based on existing information systems. Originality/value: This paper presents a case study of Metamorphosis process.